The Relationship between Smoking Behavior and the Incidence of Generalized Anxiety Disorder (GAD) in Students - Mika Tata Muzakhi; Sri Indra Kurnia (Indonesian Journal of Global Health Research, 2025)
Generalized Anxiety Disorder (GAD) is a psychological disorder characterized by excessive worry and uncontrollable responses that persist continuously and can be experienced by both men and women. The Ministry of Health indicates that 47.7% of Indonesian adolescents experience anxiety disorders. Based on data from the National Adolescent Mental Health Survey (I-NAMHS) in 2022, it was revealed that in the past year, 155 million adolescents in Indonesia suffered from mental health disorders such as anxiety disorders. This study aims to identify the correlation between smoking behavior and GAD cases among students at Muhammadiyah University Surakarta from the 2021 to 2024 cohorts. This is a quantitative study using a cross-sectional approach. The sample consists of 240 active male students at UMS. The sampling technique used was stratified random sampling. The instrument used was a standardized questionnaire from the Anxiety and Depression Association of America (ADAA), which has been translated into Indonesian and tested for validity and reliability. The questionnaire demonstrated validity and reliability with a Cronbach's Alpha value 0.938. The research data were analyzed using univariate analysis to determine the characteristics of the respondents, such as age, class, and faculty. Bivariate analysis was performed using the Chi-square test. Bivariate analysis was conducted on the dependent and independent variables, namely the relationship between smoking behavior and GAD, as well as an additional test on the variable of the number of cigarettes consumed per day. The statistical test results indicate that there is no significant correlation between smoking behavior and GAD incidence with a value of (P = 0.090). Meanwhile, the test results on the relationship between the number of cigarettes consumed per day and GAD incidence show a weak correlation with a value of (P = 0.010).